2020
DOI: 10.1002/oby.22718
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mental Health–Related Quality of Life Changes Among Insurer Subgroups Following Bariatric Surgery

Abstract: Objective This study sought to determine improvements in mental and physical health–related quality of life (HRQOL) following bariatric surgery in Medicaid and commercially insured patients. Methods Using data from the Longitudinal Assessment of Bariatric Surgery, an observational cohort study of adults undergoing bariatric surgery (2006‐2009), changes in Short Form 36 mental component summary (MCS) and physical component summary (PCS) scores were examined in 1,529 patients who underwent Roux‐en‐Y gastric bypa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
(36 reference statements)
2
2
0
1
Order By: Relevance
“…In the short-term follow-up (1-2 years), authors report comparable outcomes with significant improvement of QoL after both LSG and LRYGB [40,41]. A study by Takemoto et al reported significant improvement in both mental and physical aspects of QoL 1 year after bariatric procedures, which remained stable during the following 5 years [42]. Our results did not show a significant difference in QoL improvement between groups undergoing LSG an LRYGB 1 year after surgery.…”
Section: Discussionsupporting
confidence: 53%
“…In the short-term follow-up (1-2 years), authors report comparable outcomes with significant improvement of QoL after both LSG and LRYGB [40,41]. A study by Takemoto et al reported significant improvement in both mental and physical aspects of QoL 1 year after bariatric procedures, which remained stable during the following 5 years [42]. Our results did not show a significant difference in QoL improvement between groups undergoing LSG an LRYGB 1 year after surgery.…”
Section: Discussionsupporting
confidence: 53%
“…Similarly, the positive correlation between ankle dorsiflexion and HADS Anxiety at the 2-month mark highlights the intricate relationship between physical recovery and psychological well-being. These findings are in line with current literature which emphasizes the holistic nature of patient recovery, suggesting that physical improvements post-surgery can have far-reaching effects on mental health and overall quality of life [40,41]. The correlation analysis in our study not only confirms these established notions but also provides a nuanced understanding of how specific clinical interventions like screw removal in tibiofibular diastasis can influence various dimensions of patient health.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are supported by two recent American prospective cohort studies [45,46]. The Utah Obesity Study examined 12-year changes in HRQL in people undergoing RYGB compared with people with severe obesity who sought (but did not undergo) surgery and those who did not seek bariatric surgery [45].…”
Section: Impact Of Bariatric Surgery On Generic Hrqlmentioning
confidence: 64%
“…Limitations of this study were the large amount of missing HRQL data at 12-year follow-up, with important baseline differences noted between completers and non-completers [ 45 , 47 ]. The multi-centre Longitudinal Study of Bariatric Surgery (LABS) reported SF-36 scores up to 5 years post-surgery in 1529 people who underwent RYGB, SG and AGB (comparisons between procedures were not made) [ 46 ]. Clinically meaningful improvements in PCS were found at 1-year post-surgery followed by relatively stable levels between 1 and 5 years.…”
Section: What Do We Know About the Impact Of Bariatric Surgery On Hrqmentioning
confidence: 99%